Beyond migrants and stayers: Reimagining rurality as a dynamic space of mobility - Zhong, Hanyue (Australian and International Journal of Rural Education, 2025)
This article examines rural youth mobility in China through Yu’s story, a young woman who simultaneously calls three places ‘home’. First, the story unsettles conventional categories of stayers and leavers in the migration framework. Yu’s trajectory highlights how negotiations between family responsibilities and structural constraints, rather than just individual aspirations, become the key determinants of rural youth mobility. Second, it challenges the stability and fixity assumptions embedded in the cultural construction of rurality. By focusing on Yu’s transportation practices, from electric bike rides within the village to long-distance bus journeys between towns, the article reveals how rural places are traversed in the complex and dynamic process of everyday mobility, showing how the appearance of stability in rural life is inherently dynamic and fluid. The article argues for recognising rurality as a generative space of connection and mobility, challenging urban-centred assumptions about rural youth mobility.